Efficacy of modified pharmacomechanic thrombolysis for endovascular treatment of thrombosed arteriovenous grafts - 张丽红; 詹申; 肖光辉; 王玉柱; 刘文虎 (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy and safety of the PMT technique in the treatment of thrombosed PAVA by analyzing the long-term patency.Methods Patients who were treated in our hospital for PAVA thrombosis from August 2018 to September 30,2019 were selected,and qualified patients were treated with modified pulsed-spray pharmacomechanical thrombolysis by the same surgeon.Baseline data and surgical information were collected and followed up for 180 days.Observe the postoperative patency and analyze the factors affecting the primary patency.Results A total of 105 patients underwent thrombectomy,with an average total operation time of（66.65±10.08）minutes,blood flow opening time of（16.75±4.28）minutes,and a dosage of urokinase of（27.9±8.05）ten thousand U.The technical success rate was 97.94%,and the clinical success rate 97.26%.The total complication rate was 6.85%,no symptoms pulmonary embolism and arterial embolism.The postoperative primary patency rates were 91.55%,70.42%,and 42.95% at 30,90,and 180 days,the postoperative primary assisted patency rates were 93.66%,82.39%,and 59.15%.Cox analysis showed high cholesterol（HR 1.08,P=0.02）,type of vascular prosthesis（HR 2.14,P<0.01）,and combined stenosis（HR 5.23,P<0.01） were the risk factors affecting the primary patency after PAVA thrombus intervention.Conclusion The modified PMT technique is effective and safe in endovascular treatment of thrombosed PAVA.It is time-saving,lower cost,simple operation,which is worthy of clinical application.